Determination of calcium and magnesium in hydroethanolic extracts of propolis by atomic absorption flame spectrophotometry - Santana, Efigenia Q.; Almeida, A. A. [UNESP]; Jabor, A. P.; Almeida, Adelia Emilia de [UNESP]; Chung, M. C. [UNESP] (My University, 2008)
Propolis is a natural product collected by honeybees and has a large range of pharmacological activity, including antimicrobial, antitumoral, antioxidant and anti-inflammatory. Its use as a popular medicine is increasing all over the world, creating a need for quality control of the commercial products. In this study the levels of calcium and magnesium in commercial hydroalcoholic propolis extracts from varies states of Brazil were determined by atomic absorption flame spectrophotometry and different values were obtained for northern and southern states. This study can be extended to the analysis of metals that are harmful to health. The results showed that the calibration curves were linear over a wide concentration range (0.5-4.0 μg.mL -1 for calcium and 0.05-0.4 μg.mL -1 for magnesium) with good correlation coefficients (0.999 and 0.988, respectively). Good analytical recovery (94%) was obtained. The proposed method showed adequate precision and relative standard deviation lower than 2 %. The method is accurate and precise as well as having advantages such as simplicity and speed.
Keywords: Analysis; Calcium; Hydroalcoholic propolis extract; Magnesium; Mineralization; calcium; magnesium; propolis; antiinflammatory activity; antimicrobial activity; antineoplastic activity; antioxidant activity; atomic absorption spectrometry; calibration; correlation coefficient; drug activity; health hazard; nonhuman; quality control